2008
DOI: 10.1210/jc.2008-0330
|View full text |Cite
|
Sign up to set email alerts
|

Value of Fractional Uric Acid Excretion in Differential Diagnosis of Hyponatremic Patients on Diuretics

Abstract: FE-UA allows the diagnosis of SIAD with excellent specificity. Combining the information on U-Na and FE-UA leads to a very high diagnostic accuracy in hyponatremic patients with and without diuretic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 31 publications
3
108
2
4
Order By: Relevance
“…Several studies have used test infusions of isotonic saline to discriminate between these alternatives, but because our study was retrospective, we were unable to use this test. 11,20 Some studies have reported that, in patients in a state of volume depletion, volume repletion removes the stimulus for antidiuretic hormone release, allowing excess water to be excreted in a dilute urine and the serum sodium concentration to return toward normal. 21,22 According to this theory, instead of using an isotonic test infusion, we added in our study a criterion of volume depletion in which patients with a sustained increase in serum sodium concentration of !5 mEq/L and a sustained decrease in blood urea nitrogen, even with administration of hypotonic solution, were classified as volume depleted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used test infusions of isotonic saline to discriminate between these alternatives, but because our study was retrospective, we were unable to use this test. 11,20 Some studies have reported that, in patients in a state of volume depletion, volume repletion removes the stimulus for antidiuretic hormone release, allowing excess water to be excreted in a dilute urine and the serum sodium concentration to return toward normal. 21,22 According to this theory, instead of using an isotonic test infusion, we added in our study a criterion of volume depletion in which patients with a sustained increase in serum sodium concentration of !5 mEq/L and a sustained decrease in blood urea nitrogen, even with administration of hypotonic solution, were classified as volume depleted.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Clinical Outcomes The primary outcome of analysis was defined as mortality within 30 days of admission (''30-day mortality''). The secondary outcome was defined as mortality during the hospital stay (''in-hospital mortality'').…”
Section: Definition Of Hyponatremia and Its Causesmentioning
confidence: 99%
“…Elevations of blood urea nitrogen, creatinine, and uric acid level are helpful laboratory clues to the presence of volume depletion. Measuring the urine sodium excretion is considered (it should be <20 to 30 mmol/L) [19,20]. Euvolemic (normovolemic) hyponatremia which is most often associated with the SIADH also known as SchwartzBartter syndrome but can also be seen with primary polydipsia, a low dietary solute intake, renal failure and endocrine disorders such as hypothyroidism and secondary adrenal insufficiency [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…As the high FeUA usually corrects with fluid restriction in SIADH, some authors have suggested that an FeUA that remains above 10-12% in hyponatremic and hypouricemic patients, a diagnosis other than SIADH should be considered. 83,84 Thus considered it appears that intravascular volume regulates FeUA, with even small increases such as those seen in SIADH being associated with decreased URAT1/OAT activity with increased FeUA, and decreased intravascular volume being associated with increased URAT1/OAT activity and decreased FeUA.…”
Section: Uric Acidmentioning
confidence: 99%
“…Nevertheless, an FeUA above 10-12% remains an excellent tool for the diagnosis of SIADH. 83,84 Similarly, as most of the uromodulin-related diseases (familial juvenile hyperuricemic nephropathy and medullary cystic kidney disease) are associated with reduced FeUA, this can be helpful in diagnosis. 120 …”
Section: Feuamentioning
confidence: 99%